Modern aspects of the tourist industry development problem in Kazakhstan - Zholdasbekov, Abdimanat (UTMS journal of economics)
Kazakhstan land is rich with position of biological, climatic, cultural and natural variety, which promotes the tempestuous development of the tourist business. As it is well known, tourist business is a highly profitable branch to economic activity. Exactly so one of the priority direction of the economy in Kazakhstan is determined "tourist cluster". Its shaping means the development to tourist industry, making the tourist products and rendering the tourist services, which can compete on the world market.